Pengaruh Kepercayaan, Kemudahan, Dan Kualitas Informasi Terhadap Keputusan Pembelian Secara Online Di Situs Shopee.co.id Pada Konsumen Di Kabupaten Sleman - Bambang Irjanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
. The purpose of thils study was to determilne and analyze the ilnfluence of trust, ease, and qualilty of ilnformatilon on onlilne purchasilng decilsilons on the Shopee.co.ild silte for Shopee consumers iln Sleman Regency. Thils research ils a type of causal associlatilve research that ailms to analyze the relatilonshilp between one varilable and another. The populatilon iln thils study are consumers of onlilne shoppilng whose number ils unknown. The samplilng method used purposilve samplilng wilth a total sample of 80 respondents. The data analysils method used ils a quantiltatilve descrilptilve analysils method wilth multilple lilnear regressilon analysils technilques. The results of the research hypothesils testilng show that the varilables of trust, convenilence, and qualilty of ilnformatilon silmultaneously have a posiltilve and silgnilfilcant effect, then partilally the trust varilable has no posiltilve and ilnsilgnilfilcant effect, whille the ease and qualilty of ilnformatilon have a posiltilve and silgnilfilcant effect on onlilne shoppilng decilsilons iln the dilstrilct. Sleman. The Coeffilcilent of Determilnatilon test shows that 58.1% 68.1% of purchasilng decilsilons can be explailned by the varilables of trust, convenilence, and qualilty of ilnformatilon, whille the remailnilng 31.9% ils explailned by other factors not ilncluded iln thils study.